2021
DOI: 10.1186/s12889-021-11569-z
|View full text |Cite
|
Sign up to set email alerts
|

Preceding child survival status and its effect on infant and child mortality in India: An evidence from National Family Health Survey 2015–16

Abstract: Background India has achieved impressive gains in child survival over the last two decades; however, it was not successful in attaining MDG 2015 goals. The study’s objective is to inquire how the survival status of the preceding child affects the survival of the next born child. Methods This is a retrospective analysis of data from the National Family Health Survey, 2015–16. Analysis was restricted to women with second or higher-order births becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
(59 reference statements)
0
13
0
Order By: Relevance
“…Nine studies identified parents' educational status (either father's or mother's education or both) as an essential factor for calculating the risk of death of a child in families 4,9,12,13,16,27,28,34,46 . A total of 17 studies considered household religion, caste, and income as essential family‐level factors for studying death clustering 2,3,9–11,13,16,29,31–33,35–37,39,43–45 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine studies identified parents' educational status (either father's or mother's education or both) as an essential factor for calculating the risk of death of a child in families 4,9,12,13,16,27,28,34,46 . A total of 17 studies considered household religion, caste, and income as essential family‐level factors for studying death clustering 2,3,9–11,13,16,29,31–33,35–37,39,43–45 …”
Section: Resultsmentioning
confidence: 99%
“…Zaba and David argued that ‘clustering’ of deaths is due to systematic parity effects that expose children to fatalities 44 . The death of a previous child was found to be associated with the mortality risk of the index child in 11 studies 7,8,10–12,15,16,24,33,36,45 . According to a few studies conducted in India (including in Punjab 4,5 and Odisha 45 ), Mali, 46 Guatemala, 11,12 Brazil, 6,13 Bangladesh, 7,24,34–36 Senegal, 8 Nigeria, 3 and Kenya, 3,15,16,38 survival chances are more or less similar between children born into the same family and those born into different families.…”
Section: Resultsmentioning
confidence: 99%
“…When exclusive breastfeeding is done in the first six months of life, it reduces infant morbidity and mortality [2]. Its effects on child survival, growth, and maternal health are well-documented [2,3]. The natural and ideal way of feeding infants provides babies all the energy and nutrients they need for the first six months of their lives [1].…”
Section: Introductionmentioning
confidence: 99%
“…Globally, exclusive breastfeeding is promoted as the 'best newborn feeding approach' [1]. Increasing scientific data shows that exclusive breastfeeding improves baby survival [3,[7][8][9][10]. It's one of the most effective ways to minimize newborn morbidity and death in resource-limited contexts, where improper nursing techniques induce child malnutrition, a primary cause of infant mortality [1].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies viewed death clustering as being a greater heterogeneity in the distribution of child deaths across families than would be expected if the deaths were distributed randomly [ 12 , 13 , 14 , 15 ]. In addition to the above definitions, death clustering has been viewed as what is left unexplained after the observed correlates are controlled, and it is thus attributed to unobserved or unobservable genetic, behavioral, and environmental factors related to mortality [ 5 , 6 , 10 , 12 , 13 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%